SLIDING PLANE IDENTIFICATION FOR LANDSLIDE HAZARD MITIGATION WITH RESISTIVITY TOMOGRAPHY METHOD - Wibowo, Rahmat Catur; Maulia, Ikram; Haerudin, Nandi; Sarkowi, Muh (Universitas Mataram, 2023)
Pidada area, Panjang sub-district, Bandar Lampung city, located on Barisan Hill complex, has been affected by the Sumatran fault movement and the Lampung-Panjang fault so that the morphological condition is hilly with steep slopes, which causes the risk of natural disasters such as landslides. In this article, the identification of subsurface rock lithology and sliding plane in the landslide-prone zone is carried out using the Wenner-Schlumberger configuration geoelectric method. Based on the Wenner-Schlumberger configuration, the top layer has lithology clay tuff and sandy tuff, which predicted a weathered rock with a resistivity of 1 - 133 ohm.m. Coarse-grained tuff and fine-grained tuff with resistivity values of 135 - 250 ohm.m in the middle. The bottom layer has a resistivity of more than 250 ohm.m, that predicted to have a lithology breccia (igneous rock) Tarahan Formation. The sandy clay layer (81 - 90 ohm.m) predict as a sliding plane in this area at depths of 8.2 to 16 m. The type of landslide developed in the research area is a crawling soil landslide with very steep slope characteristics (80 – 350).